2016
DOI: 10.18311/ajprhc/2016/4412
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Captopril on Liver Toxicity Induced by High and Low Dose of Paracetamol in Rats:Histological Study

Abstract: Many patients may administered medications like captopril (ACE inhibitor) for treatment of chronic diseases and may also take Paracetamol as an Over The Counter (OTC) drug which may interact with captopril. Therefore, the aim of this study is to evaluate of the hepatoprotective effect of captopril on liver toxicity induced by low and high dose of paracetamol in rats. This study was conducted in two phases: first study for low dose of paracetamol (300 mg/kg); animals were divided into 4 groups of 6 rats each (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, captopril was shown by Ackerman et al (2008) to reduce the activity of glutathione reductase and peroxidase. These studies using the paracetamol-induced toxicity paradigm demonstrate that captopril has hepatoprotective properties (Al-Shaikh et al, 2016;Ali, 2012;Mahmood et al, 2014). According to Mohamed et al (2016), the main cause of liver damage is hyperglycemia-induced oxidative stress, hence a combination of losartan and captopril may be more effective in reducing it.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, captopril was shown by Ackerman et al (2008) to reduce the activity of glutathione reductase and peroxidase. These studies using the paracetamol-induced toxicity paradigm demonstrate that captopril has hepatoprotective properties (Al-Shaikh et al, 2016;Ali, 2012;Mahmood et al, 2014). According to Mohamed et al (2016), the main cause of liver damage is hyperglycemia-induced oxidative stress, hence a combination of losartan and captopril may be more effective in reducing it.…”
Section: Discussionmentioning
confidence: 99%
“…Fouad and Jresat [49] reported that CoQ10 attenuated APAP-induced hepatotoxicity via inhibiting lipid peroxidation and inducible nitric oxide (NO) synthase, thus decreasing NO production and preventing NO-induced depletion of glutathione and catalase. Al-Shaikh et al [50] reported that captopril given to rats (20 mg/kg/day orally for 10 days) has hepatoprotective effects against APAP overdose, which might be attributed to its sulfhydryl group that is not present in other ACE inhibitors that acts as a free radical scavenger. In addition, captopril is reported to ameliorate oxidative stress by enhancing total glutathione content as well as glutathione peroxidase and glutathione reductase activities in various mouse tissues [51].…”
Section: Number Of Glial Fibrillary Acid Protein Astrocytesmentioning
confidence: 99%